Alien abjection amid the morning calm a singular reading of horror films from beyond Southeast Asia - Ha, Ju-Yong (Plaridel, 2015)
Access online through this link: https://www.plarideljournal.org/article/alien-abjection-amid-the-morning-calm-a-singular-reading-of-horror-films-from-beyond-southeast-asia